Handbook of Research on Modern Educational Technologies, Applications, and Management (2 Volumes) - Khosrow-Pour, Mehdi (Information Science Reference, 2020)
This book provides cutting-edge, multidisciplinary research and expert insights on advancing technologies used in educational settings as well as current strategies for administrative and leadership roles in education. Covering a wide range of topics including but not limited to community engagement, educational games, data management, and mobile learning, this publication provides insights into technological advancements with educational applications and examines forthcoming implementation strategies